Job Search: A Multidisciplinary Review and Research Agenda. (23rd April 2015) - Manroop, Laxmikant; Richardson, Julia
Abstract : Scholarly interest in job search has grown significantly over the years and can be located in diverse research streams: namely, economics, sociology and industrial/organizational psychology. This paper reviews these bodies of literature and makes a case for integration by proposing a multidisciplinary approach to understanding job‐seeking behaviors. To this end, the paper categorizes the respective literatures on the basis of common themes located in a conceptual multidisciplinary model of job search behaviors and outcomes. This model provides a more focused understanding of the job search literature and how it has developed in the related disciplines. Based on the review and conceptual model presented, the paper draws attention to several key areas for future research to advance the field further.